Sapere e potere al tempo della crisi climatica - Mutchinick, Joaquin (Mechane, 2025)
This article aims to examine a pivotal aspect of the climate crisis: the asymmetry between knowledge and power in shaping outcomes. The focus of the study is the gap between the growing body of robust knowledge regarding the climate implications of our production and consumption patterns, on the one hand, and the ability of this knowledge to mobilize social forces, on the other. The explanation proposed – drawing on Marxian and post-Marxian reflections on ideology – argues that knowledge about the climate crisis becomes ineffective because it treats certain elements of the process as fixed and immutable. Building on the theoretical insights of the constructivist approach and analyzing a specific case study – the energy transition – the final chapter explores the conditions under which a non-ideological theory of the climate crisis becomes conceivable.